Cost-effective Simulation of the Hybrid Solar/Wind and Diesel Energy System in Rural Area - Barsoum, Nader; Sim, Ee (American Institue of Physics AIP, 2008)
This paper describes the optimization of a hybrid energy system model. Currently in Sarawak, people living in the rural areas still depend on diesel generators to generate electricity. This increases the demand for fossil fuel, creates noise pollution and toxic gas is emitted to the environment. Hence, hybrid energy systems were introduced to replace this conventional energy system as well as improving the living standard in the villages. In this paper, several hybrid energy system configurations were investigated in order to find out the most cost effective hybrid system through Hybrid Optimization Model for Electric Renewability (Homer) software. Homer simulates, optimizes, and analyzes the sensitivity variables for each of the system configurations.